IMPACT OF MALNUTRITION ON PEDIATRIC HEART FAILURE ANALYZING Z-SCORES AT PRESENTATION - YOUSAFZAI, ZA; ILYAS, S; NAWAB, Z; ABDULLAH, . (Biological and Clinical Sciences Research Journal, 2024)
Pediatric heart failure represents a critical health concern characterized by the heart's inability to effectively pump blood, often resulting from congenital heart defects, myocarditis, and cardiomyopathies. Malnutrition has emerged as a recognized comorbidity in pediatric heart failure, significantly impacting patient outcomes. This study aimed to investigate the relationship between malnutrition and pediatric heart failure by analyzing Z-scores at presentation to guide targeted interventions and improve patient management. The study employed a retrospective observational design and was conducted at the Department of Pediatric Cardiology, Lady Reading Hospital, Peshawar, from January 2023 to January 2024. A total of 764 pediatric patients with heart failure were included in the analysis. Nutritional status was assessed using weight and height measurements, and Z-scores were calculated based on WHO Child Growth Standards. Data analysis was performed using IBM SPSS version 22. Results revealed varying degrees of malnutrition among pediatric heart failure patients, with 62.8% classified as severely malnourished, 28.4% as moderately malnourished, and 8.8% as mildly malnourished. The calculated Z-score of -3.2 indicated significant malnutrition among the study population. Furthermore, a negative correlation (r = -0.32, p < 0.001) between Z-score and left ventricular ejection fraction was observed, suggesting a link between malnutrition severity and cardiac dysfunction. These findings underscore the high prevalence of malnutrition among pediatric heart failure patients and its substantial impact on outcomes. Early nutritional assessment and intervention are crucial for optimizing patient care and enhancing outcomes in children with heart failure. Collaborative, multidisciplinary approaches that integrate cardiac and nutritional management strategies can comprehensively address the diverse needs of this vulnerable population.